Evaluation of clinical, radiological and pathological correlation of sino-nasal masses: our experience - Patni, Digant; Yadav, Shobit; Prajapati, Kamal K.; Munjal, V. R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Purpose of study was to evaluate clinical, radiological, pathological correlation of sinonasal masses, to correlate age and sex with etiology of sinonasal masses and to evaluate percentage of patient having malignancy. Methods: This was a hospital based prospective observational study. In this study total numbers of 69 cases of sinonasal mass were selected from those patients who were admitted in department of otorhinolaryngology and head and neck surgery SAMC and PGI Indore MP from June 2019 to August 2021. Results: Sinonasal masses are more common in 4th to 6th decade, males, farmers and lower socioeconomic status. Most common presented symptom with sinonasal mass was nasal obstruction. Patients shows polypoidal mass in nasal endoscopy, which was most common finding. Most of the patients radiological scan shows the opacity. 26.1% cases were neoplastic and rest non neoplastic. These rules however, may be broken in sinonasal imaging. The relative number of non-neoplastic and neoplastic lesions varies from region to region. A provisional diagnosis was made after clinical assessment and radiological investigation but final diagnosis was made after histopathological examination. Conclusions: From the above study, it is clear that radiological examination and nasal endoscopy is helpful and important adjunct to overall clinicopathological evaluation of patients but it is not free of fallacies. Hence a thorough radiological, clinicopathological evaluation with pre op endoscopic evaluation and histopathology is necessary for better management of patients presenting with sinonasal masses.